KREATIVITAS GURU PENJAS SD DALAM MENYIKAPI KETERBATASAN SARPRAS SE-KECAMATAN WONOSEGORO (Indonesian Journal for Physical Education and Sport, 2021)
Initial observations found that teachers are not optimal in overcoming the limitations of physical education learning facilities and infrastructure, not all of them empowering their creativity in modifying physical education facilities and infrastructure which are still limited. The purpose of this study was to determine the creativity of physical education teachers in responding to the limitations of physical education facilities and infrastructure in Wonosegoro District, Boyolali Regency. This research is a descriptive quantitative research that uses a survey method with data collection techniques using a questionnaire. The population of this study were all teachers of physical education, sports and health, who teach at State Elementary Schools in Wonosegoro District, Boyolali Regency with a background in physical education totaling 19 teachers. The results of the study obtained that The creativity of elementary school physical education teachers in addressing the limitations of physical education facilities and infrastructure in Wonosegoro District, Boyolali Regency, there are 1 teacher (5%) in the very high category, 7 teachers (37%) in the high category, 4 teachers (21%) in the medium category, 5 teachers (26%) in the low category, and 2 teachers (11%) in the very low category. Based on the factors, namely: (1) Ability to see problems in the medium category (58%), (2) Creativity ability (originality) in the medium category (32%), 3) The ability to accept and be open to new things in the category high (47%).